SYNTHESIS OF ROBUST OPTIMAL CONTROL PROGRAM FOR AXIAL FLOW COMPRESSOR TURNING GUIDE VANES - Ugryumova, Kateryna; Meniailov, Ievhen; Trofymova, Iryna; Ugryumov, Mykhaylo; Myenyaylov, Andriy (International Journal of Computing, 2020)
The method of solving the selecting turning guide vanes law of control problem for the multistage axial flow compressor is proposed in order to ensure maximum efficiency along the operating line while maintaining specified stability margins under the uncertainty of input data. The problem under consideration belongs to a class of multi-objective stochastic optimization problems with mixed conditions. Evolutionary computational method of solution synthesis of the problems belonging to this class is developed based on the genetic algorithm. The implementation example of proposed method for selecting law of control for turning inlet at first four stages guide vanes of multistage axial flow compressor (MSAFC) of modern helicopter jet engine is considered. The problem of technological tolerance selecting the stagger angles of compressor blade rows in order to provide the specified confidence intervals based on integral performance parameters is solved. The examples of solving the problem using determined and stochastic formulations are given.